Pain Resolution After Hallux Valgus Surgery. (October 2016) - Chen, Jerry Yongqiang; Ang, Benjamin Fu Hong; Jiang, Lei; Yeo, Nicholas Eng Meng; Koo, Kevin; Singh Rikhraj, Inderjeet
Background: Although more than 1500 publications on hallux valgus can be found in the current literature, none of them have reported on the course of pain resolution after hallux valgus surgery. Thus, this study aimed to investigate pain resolution after hallux valgus surgery and to identify predictive factors associated with residual pain at 6 months after surgery. Methods: We prospectively followed up 308 patients who underwent hallux valgus surgery at a tertiary hospital at 6 months and 2 years after surgery. Multivariate logistic regression analysis was performed to evaluate the risk factors associated with residual pain after surgery. Results: Ninety-four patients (31%) had some degree of residual pain at 6 months after surgery. After excluding 4 patients who developed osteoarthritis of the first metatarsophalangeal joint over the next 18 months, 73 of the remaining 90 (81%) experienced improvement in visual analog scale (VAS) by the 2-years follow-up. Their median VAS improved from 4 (interquartile range [IQR] 3, 5) at 6 months to 0 (IQR 0, 3) at 2 years ( P < .001). A higher preoperative VAS increased the risk of having persistent pain at 6 months after sugery (odds ratio [OR] 1.388, 95% confidence interval [CI] 1.092, 1.764, P = .007), whereas a higher preoperative Mental Component Score of SF-36 (MCS) reduced this risk (OR 0.952, 95% CI 0.919, 0.987, P = .007). Conclusions: As much as 31% of patients will have residual pain at 6 months after surgery. Preoperative VAS and MCS are predictors for residual pain. However, these patients will continue to improve over the next 18 months, with 71% of them being pain free at 2 years after surgery. Level of Evidence: Level II, prospective comparative study.